2010
DOI: 10.1213/ane.0b013e3181d74898
|View full text |Cite
|
Sign up to set email alerts
|

The Epidemiology of Postpartum Hemorrhage in a Large, Nationwide Sample of Deliveries

Abstract: PPH is a relatively common complication of delivery and is associated with substantial maternal morbidity and mortality. It is increasing in frequency in the United States. PPH caused by uterine atony resulting in transfusion often occurs in the absence of recognized risk factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
424
17
23

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 563 publications
(486 citation statements)
references
References 19 publications
22
424
17
23
Order By: Relevance
“…The relative low rate of PPH and severe PPH in the present study may be attributed to the fact that the present study was focused only on primary PPH. Although rates of severe PPH vary according to the definition used and the severity of the hemorrhage, recent studies have shown that severe PPH appears to be increasing in some developed countries [5,14]. Increase in occurrence of severe PPH could be explained in partly by changes in rates of cesarean delivery, induction of labor or by increases in maternal age or body mass index [5].…”
Section: Discussionmentioning
confidence: 99%
“…The relative low rate of PPH and severe PPH in the present study may be attributed to the fact that the present study was focused only on primary PPH. Although rates of severe PPH vary according to the definition used and the severity of the hemorrhage, recent studies have shown that severe PPH appears to be increasing in some developed countries [5,14]. Increase in occurrence of severe PPH could be explained in partly by changes in rates of cesarean delivery, induction of labor or by increases in maternal age or body mass index [5].…”
Section: Discussionmentioning
confidence: 99%
“…2 Haemorrhage is the most common cause for maternal critical care admission [3][4][5] and places a profound health burden on the childbearing population during an important life event. Haemorrhage is more common in women who have caesarean sections, 6 particularly when indicated for conditions such as placenta praevia (low-lying placenta) or when an emergency caesarean section is required. 7 Approximately 166,000 caesarean sections are performed annually in England.…”
Section: Haemorrhage and Caesarean Sectionmentioning
confidence: 99%
“…In addition, numerous studies have shown, in industrialized countries, an increase in the incidence of postpartum hemorrhage in recent years [5], reflecting in part the changes in obstetrical practice of the last decade (for example, the increase in the rate of caesarean sections or the increased trend toward practice of spontaneous delivery after caesarean section).…”
Section: Introductionmentioning
confidence: 99%